Expression of goat RNA binding protein (NANOS2), development and evaluation of anti-NANOS2 IgY antibodies - X. Yao; H. Ren; W. Yang; T. Diraviyam; F. Tang; M. Yu; J. Hua; X. Zhang; S. Peng (Czech Journal of Animal Science, 2015)
Available rabbit anti-NANOS2 antibodies failed to recognize the NANOS2 protein of goat origin though they showed better reactivity towards the same protein of human and mice origin. A specific antibody against goat NANOS2 is necessary to explore the biological functions of dairy goat NANOS2 protein. Recombinant NANOS2 protein (dairy goat origin) was expressed in E. coli (BL21). Anti-NANOS2 immunoglobulin Y (IgY; in chicken) was developed and evaluated. NANOS2 protein sequences between mice and dairy goat were compared using bioinformatics tools. The specific IgY titer attained the peak (≥ 1 : 128 000) after the 3rd booster injection, then it gradually decreased to 1 : 16 000 and remained stable. The specificity and sensitivity of anti-NANOS2 IgY was superior to rabbit anti-NANOS2 IgG. Though, the functional domain 63-116 or 62-115 of NANOS2 protein is highly conserved with 100% identity in dairy goat and mice, the considerable difference in sequence at region 18-61 was identified from the predicted epitopes. According to our survey, this is the first report on preparation of chicken IgY against NANOS2 protein and indicating the prerequisite of species specific NANOS2 antibodies due to epitopes difference in functionally conserved NANOS2 protein. Anti-NANOS2 IgY could be applied as a novel research tool in developmental biology.